2006
DOI: 10.1016/j.febslet.2006.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Flavohemoglobin requires microaerophilic conditions for nitrosative protection of Staphylococcus aureus

Abstract: Flavohemoglobins and flavodiiron proteins are two families of enzymes involved in nitrosative detoxification. However, the physiological oxygen-related conditions under which they work and their relative role are still a matter of debate. To address this question we analyzed the function of the putative flavohemoprotein of Staphylococcus aureus, an organism that lacks a flavodiiron-like gene. In this report we show that the recombinant protein contains all features typical of canonical flavohemoglobins and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…First, SrrAB is essential for full induction of the flavohemoprotein Hmp. This enzyme detoxifies NO˙to nitrate, thereby reducing intracellular NOl evels such that respiration can resume (58). Reduced Hmp production in a ⌬srrAB mutant presumably extends the period of time during which NO˙levels surpass the threshold that limits respiration.…”
Section: Resultsmentioning
confidence: 99%
“…First, SrrAB is essential for full induction of the flavohemoprotein Hmp. This enzyme detoxifies NO˙to nitrate, thereby reducing intracellular NOl evels such that respiration can resume (58). Reduced Hmp production in a ⌬srrAB mutant presumably extends the period of time during which NO˙levels surpass the threshold that limits respiration.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work had shown that the primary mechanism of action of flavohemoglobins, such as HmpA, is through dinitrosylation of NO, a reaction that is dependent on O 2 (28). Hmp of Escherichia coli also possesses an O 2 -independent NO reductase activity in vitro (29), but the activity is slow, and its physiological relevance is uncertain (30). Thus, we hypothesized that under anaerobic conditions, the effect of HmpA in V. cholerae might be less dominant and NnrS might become more important.…”
Section: Nnrs Is Important For Resistance To No But Does Not Remove Nomentioning
confidence: 99%
“…Consequently, an srrAB mutant exhibited enhanced sensitivity to NO and this was partially attributed to dysregulation of the NO detoxification enzyme Hmp (see above), but the divergently transcribed ldh1 gene, encoding lactate dehydrogenase was subsequently shown to be essential for virulence and maintaining redox balance during nitrosative stress. 153,154 The overlap between the response to anoxia and exposure to NO could be accounted for by NO-mediated inhibition of aerobic respiration triggering the activation of the SrrAB two-component system and consequently the role of SrrAB could be extended beyond the control of hypoxic metabolic and major virulence factor genes to include NO resistance; a combination that readily explains the attenuation of the srrAB mutant.…”
Section: Nitric Oxide Responsesmentioning
confidence: 99%